Searching for Judgment Biases Among Elite Basketball Referees - Morgulev, Elia; Azar, Ofer H.; Lidor, Ronnie; Sabag, Eran; Bar-Eli, Michael (Frontiers in Psychology, 2018)
An attacking basketball player initiating significant physical contact with a defender who has already established a legal and stationary position, should be called with an offensive foul. Offensive foul situations are particularly ambiguous and complex, making the referee’s task a difficult one. In such conditions of complexity and constraints of time, the referee is likely to be prone to systematic biases, as has been documented by previous research in other sport settings. We analyzed the referees' decisions in 250 instances of collisions between an attacking player and a defender. In these collisions the defender fell, and potentially an offensive foul could be called. We found no evidence of favoritism granted to the home team, to star players, or to high-reputation teams, or of small players being tackled by significantly larger opponents. The findings suggest that these biases are not very robust, and are sensitive to the context, and that proper training of referees and enhanced awareness can help to alleviate referees’ biases.